2007
DOI: 10.1007/s10620-007-9884-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Patients with Liver Cirrhosis Who Underwent Curative Surgery for Gastric Cancer: A Retrospective Multi-center Study

Abstract: We investigated early postoperative morbidity, mortality, and long-term outcomes in patients with liver cirrhosis (LC) who had undergone curative surgery for gastric cancer. The medical records of patients with LC who had undergone radical gastrectomy for gastric adenocarcinoma between January 1996 and September 2006 were retrospectively reviewed. A total of 57 patients were enrolled in this study. Forty-six patients (81%) were classified into Child's class A. In 22 patients (39%) postoperative complications d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Therefore, it is difficult to determine whether cirrhotic patients are suitable for gastric cancer treatment, for which the prognosis is comparatively good. Several studies have focused on the clinical outcomes of radical gastrectomy for patients with gastric cancer and comorbid LC [21][22][23][24][25][26]. These studies indicate that 10-20 % of LC patients develop post-operative intractable ascites, and perioperative mortality is approximately 10 %.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult to determine whether cirrhotic patients are suitable for gastric cancer treatment, for which the prognosis is comparatively good. Several studies have focused on the clinical outcomes of radical gastrectomy for patients with gastric cancer and comorbid LC [21][22][23][24][25][26]. These studies indicate that 10-20 % of LC patients develop post-operative intractable ascites, and perioperative mortality is approximately 10 %.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of death for gastric cancer patients with Child A cirrhosis and Child B or C were usually related to gastric cancer recurrence and liver failure/hepatocellular carcinoma, respectively [4, 16]. Therefore, D2 lymph node dissection can be recommended for gastric cancer patients with Child A cirrhosis while less than D2 lymph node dissection can be considered for gastric cancer patients with Child B or C. Furthermore, hepatocellular carcinoma can develop in early gastric cancer patients with liver cirrhosis after gastric cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The study presented radical open gastrectomy with extended lymph node dissection as feasible in patients with compensated liver cirrhosis [3]. For patients with moderate to severe hepatic dysfunction, however, D1 or less extensive lymph node dissection with meticulous hemostasis may be the more reasonable surgical procedure, and radical gastrectomy is very dangerous, even fatal, for Child C patients [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…In case of abdominal surgery, patients with LC often undergo severe complication such as hepatic failure, massive ascites, intra-abdominal bleeding, multi-organ failure, and sepsis 13,22. Some studies reported high mortality rate of up to 30% in these patients 23,24.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that open gastrectomy is associated with high complication and mortality rates in patients with severe liver dysfunction. Jang et al22 reported the clinical outcomes after curative surgery for gastric cancer in patients with LC. In their study, postoperative ascites (63.6% vs 13%) and hepatic encephalopathy (36.4% vs 4.3%) occurred significantly more frequently in patients with Child-Pugh class B or C than in those with class A.…”
Section: Discussionmentioning
confidence: 99%